A Critical Review of the House of Representatives’ Role in the Naturalization Process of Foreign Athletes in Indonesia - Muhammad Fathur Rizqi; Mochammad Adli Wafi (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2025)
In the Citizenship Law in Indonesia, there are three regulated citizenship pathways, namely Ordinary Naturalization (Article 9), Naturalization due o Mixed Marriage (Article 19), and Special Naturalization (Article 20). In its implementation, only the Special Naturalization pathway involves the role of the People’s Representative Council of the Republic of Indonesia (DPR) in the process of granting citizenship. This study attempts to analyze the original intent of the DPR’s recommendation, position, and benchmarks in the process of granting citizenship to Foreign Athletes. The purpose of this study is to describe the involvement of the DPR in the process of granting citizenship to Foreign Athletes within the framework of laws and regulations in Indonesia. This study uses a juridical-normative research method based on academic manuscripts, minutes of meetings, and provisions of lawsand regulations in Indonesia. In addition, this study uses three approaches, namely the legislative approach, the conceptual approach, and the historical approach. Furthermore, this study found that the involvement of the DPR in the process of naturalizing Foreign Athletes in Indonesia is a form of preventive supervision is measuring national interests and preventing abuse of authority. However, there is still ambiguity regarding the DPR’s consideration of national interests, so clear criteria are needed to measure national interests. In addition, there needs to be clearer rules regarding the legal implications related to the DPR’s rejection of citizenship applications through the special naturalization route.